Soft Regular Generalized ω-Closed Sets and Soft ω-T1/2 Spaces - Samer Al Ghour (Axioms, 2022)
Soft <semantics>rgω</semantics>-closed sets are introduced as a new class of soft sets that strictly contain the classes of soft <semantics>rg</semantics>-closed sets and soft <semantics>gω</semantics>-closed sets. Furthermore, the behavior of soft <semantics>rgω</semantics>-closed sets with respect to soft unions, soft intersections, and soft subspaces, as well as induced soft topologies are investigated. Moreover, soft <semantics>ω</semantics>-<semantics>T1/2</semantics> spaces which is a weaker form soft <semantics>T1/2</semantics> spaces is defined and investigated. In addition to these, the characterizations of soft <semantics>rg</semantics>-<semantics>T1/2</semantics> spaces and soft <semantics>rgω</semantics>-<semantics>T1/2</semantics> spaces are discussed. The work also looks at the relationship between our novel notions in soft topological spaces and their analogs in topological spaces.